2019
DOI: 10.1038/s41598-019-40936-5
|View full text |Cite
|
Sign up to set email alerts
|

Ecological processes underpinning microbial community structure during exposure to subinhibitory level of triclosan

Abstract: Ecological processes shaping the structure and diversity of microbial communities are of practical importance for managing the function and resilience of engineered biological ecosystems such as activated sludge processes. This study systematically evaluated the ecological processes acting during continuous exposure to a subinhibitory level of antimicrobial triclosan (TCS) as an environmental stressor. 16S rRNA gene-based community profiling revealed significant perturbations on the community structure and dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Interestingly, species of this family have been determined as potential degraders of IBP, DCF, and naproxen . Oh et al (2019) also found enrichment of Xanthomonadaceae in TCS -amended activated sludge reactors, specifically of the genus Pseudoxanothomonas. Żur et al (2018) reported that Pseudoxanthomonas spadix BD-a59, a species with the ability to degrade all six BTEX (benzene, toluene, ethylbenzene, and o-, m-, and p-xylene) compounds, has a gene cluster with a high similarity with ibuprofen degradation genes ipfABDEF.…”
Section: Impact Of Ppcps On the Composition Of The Bacterial Communitiesmentioning
confidence: 77%
See 1 more Smart Citation
“…Interestingly, species of this family have been determined as potential degraders of IBP, DCF, and naproxen . Oh et al (2019) also found enrichment of Xanthomonadaceae in TCS -amended activated sludge reactors, specifically of the genus Pseudoxanothomonas. Żur et al (2018) reported that Pseudoxanthomonas spadix BD-a59, a species with the ability to degrade all six BTEX (benzene, toluene, ethylbenzene, and o-, m-, and p-xylene) compounds, has a gene cluster with a high similarity with ibuprofen degradation genes ipfABDEF.…”
Section: Impact Of Ppcps On the Composition Of The Bacterial Communitiesmentioning
confidence: 77%
“…Recent studies have demonstrated that TCS is an environmental stressor, alters the community structure and reduces species diversity and richness (Clarke et al, 2019;Oh et al, 2019;Peng et al, 2019). The simultaneous treatment with the three PPCPs gave alpha diversity values generally lower than those obtained for IBP and DCF, and higher than for TCS alone, but not significantly different from the controls, except for a higher evenness after 7 days.…”
Section: Bacterial Richness and Diversity In The Bps Microcosmsmentioning
confidence: 87%
“…Understanding this response can be critical, among others, for rational therapeutics to mitigate unwanted effects on patient health caused by changes in the gut microbiota (e.g. Clostridioides difficile infection 6 ), management of waste water treatment to ensure the maintenance of key functionalities in bacterially driven processes 7 , and redesigning of agricultural practices to maintain microbiota contributing to crop health and productivity 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The larger proportion of sensitive than tolerant taxa in all treatments suggested that the microbial community was not robust to the persistence of micropollutants in its surroundings. Noteworthily, two strictly tolerant genera across treatments were Sphingomonas and Hydrogenophaga (Table S4), which have been shown to be enriched in the BPA or TCS-contaminated environments (Oh et al, 2019;Zaborowska et al, 2020;Hagberg et al, 2021) and to produce enzymes capable of degrading different pollutants (Gao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%